(3OjhGf HgGA GdOjf RgjQs - (3GdHgGA RgjQ , RgjQ Hf eMeO Hf Ydj GdegdHj GdUGdMj, HgGA GdOjf,J (B656 (3g` s
(3ChdgG (B:s
(3CeG HYO abO SN dj Cf CPcQ aj gPg GdChQGb eG hbY dj ef GdJcde aj Ref GdTHGH Ydi MQha GdoeYLe dojSgd GdCeQ Ydi GdWdGH hGddg GdegjF ddCSHGH s
(3BNQgG (B:s
(3hLdjS MOjKg ddeSQGJ WGQO eKd djd GdTJG agh Whjd hHGQO s
(3bWYI ef fSNI NGeSIs
(3HgG BKGQ JShjSs
(3hQO CjVkG JMJ Qbe (B2202s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B52s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B49 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B780s
Keywords: (3GdCOHs